Probabilistic reanalysis of twentieth-century sea-level rise - Hay, Carling C.; Morrow, Eric; Kopp, Robert E.; Mitrovica, Jerry X. (Nature (London), 2015)
A statistical reassessment of the tide gauge record concludes that sea level rose at a rate of about 1.2 millimetres per year from 1901 to 1990, slightly lower than prior estimates and now consistent with estimates based on individual contributions to sea-level change; the estimates reported here from 1990 onwards are consistent with other work, suggesting that the recent acceleration in sea-level rise is greater than previously thought. Twentieth century sea levels revisited Rates of sea-level rise calculated from tide gauge data tend to exceed bottom-up estimates derived from summing loss of ice mass, thermal expansion and changes in land storage. Carling Hay et al . provide a statistical reassessment of the tide gauge record — which is subject to bias due to sparse and non-uniform geographic coverage and other uncertainties — and conclude that sea-level rose by about 1.2 millimetres per year from 1901 to 1990. This is slightly lower than prior estimates and is consistent with the bottom-up estimates. The same analysis applied to the period 1993–2010, however, indicates a sea-level rise of about three millimetres per year, consistent with other work and suggesting that the recent acceleration in sea-level rise has been greater than previously thought. Estimating and accounting for twentieth-century global mean sea-level (GMSL) rise is critical to characterizing current and future human-induced sea-level change. Several previous analyses of tide gauge records 1 , 2 , 3 , 4 , 5 , 6 —employing different methods to accommodate the spatial sparsity and temporal incompleteness of the data and to constrain the geometry of long-term sea-level change—have concluded that GMSL rose over the twentieth century at a mean rate of 1.6 to 1.9 millimetres per year. Efforts to account for this rate by summing estimates of individual contributions from glacier and ice-sheet mass loss, ocean thermal expansion, and changes in land water storage fall significantly short in the period before 1990 7 . The failure to close the budget of GMSL during this period has led to suggestions that several contributions may have been systematically underestimated 8 . However, the extent to which the limitations of tide gauge analyses have affected estimates of the GMSL rate of change is unclear. Here we revisit estimates of twentieth-century GMSL rise using probabilistic techniques 9 , 10 and find a rate of GMSL rise from 1901 to 1990 of 1.2 ± 0.2 millimetres per year (90% confidence interval). Based on individual contributions tabulated in the Fifth Assessment Report 7 of the Intergovernmental Panel on Climate Change, this estimate closes the twentieth-century sea-level budget. Our analysis, which combines tide gauge records with physics-based and model-derived geometries of the various contributing signals, also indicates that GMSL rose at a rate of 3.0 ± 0.7 millimetres per year between 1993 and 2010, consistent with prior estimates from tide gauge records 4 . The increase in rate relative to the 1901–90 trend is accordingly larger than previously thought; this revision may affect some projections 11 of future sea-level rise.